The disease and reinforcement of slanting cross shaped arch bridge. (December 2018) - Jiang, Tao; Wang, Huili; Zhang, Zhe; Qin, Sifeng; Xu, Fei
Abstract: The disease and reinforcement of a slanting cross-shaped arch bridge are addressed. Tongtai Bridge is a slanting cross-shaped arch bridge. After 9 years of opening to traffic, cracks are found on top of the west capping beam and the east deck migrates towards the north about 200 mm. A space finite element model is established with RM Bridge and the results of limit pins are investigated. The main cause of the bridge damage is incompetence of resisting horizontal forces. According to the cause, some reinforcement measures are adopted, which include welding new bottom plate, wrapping capping beam with steel plate, recovering the girder by tensioning and welding new limit pins under the strengthened girder bottom. After changing constraint, the bridge is safe due to horizontal forces decrease. This provides a reference for similar bridge design. Highlights: The girder of a slanting cross-shaped arch bridge bears enormous horizontal force. Horizontal force causes some bridge disease. Releasing the girder rotation restriction can reduce the horizontal force.